Nation in Conflict, Gender in Conflict. How do Syrian activists reflect on gender identities challenged by the civil war? - Petzelberger, Sophie (Momentum Quarterly, 2017)
Narratives of nation and gender identities intersect in many dimensions. In times of national conflict, they are re-negotiated, causing lasting change. This paper looks at Syria, as a case study. Calling for a feminist and post-colonial anthropology, voices of five Syrian women, speaking as political activists, are used as primary sources of research.
Keywords: gender identity; nation; Syria